THE IMPROVEMENT OF READING COMPREHENSION THROUGH SKIMMING AND SCANNING TECHNIQUES SKILLS - Fadli, Muhammad (Institute of Research Institutions and Community Service (LPPMP) of STKIP PGRI Bandar Lampung, 2024)
This study investigates the impact of skimming and scanning techniques on the improvement of reading comprehension. Skimming involves quickly reading a text to get the general idea, while scanning focuses on locating specific information. Both techniques are commonly used to enhance efficiency in reading and to improve understanding, particularly in academic and professional settings. The research explores how these methods help readers to better grasp the main points, identify key details, and boost overall reading speed. The findings indicate that students who apply skimming and scanning strategies show significant improvement in their reading comprehension skills, particularly in terms of accuracy and time management. This paper concludes that incorporating these techniques into reading practices can be an effective way to enhance reading comprehension.